Understanding and Application of Spousal Rights and Obligations Based on Surah Al-Nisa’ Verse 34 in Simpang Kiri, Aceh - Muharram, Muharram; Riswana, Riswana; Nafil, Zuhhad; Alkhair, Zia (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
Marriage in Islam aims to create a harmonious family rooted in the principles of sakinah (tranquility), mawaddah (love), and rahmah (compassion). However, a limited understanding of spousal rights and obligations—especially in Simpang Kiri Subdistrict, Subulussalam City, Aceh—often leads to conflicts that can culminate in divorce. This study analyzes the local community’s perceptions and practices regarding marital rights and obligations as outlined in Surah Al-Nisa’, verse 34, while also evaluating the impact of local customs on household dynamics. Employing a qualitative field research approach, data were gathered through semi-structured interviews and observations with community members, religious leaders, and officials from the local Office of Religious Affairs (KUA). The findings indicate that the community’s understanding of spousal rights and obligations primarily focuses on tangible aspects such as financial support and mahr (dowry), often overlooking the essential Islamic values of justice and compassion. Additionally, local customs significantly shape marital practices, frequently resulting in inconsistencies with Islamic principles. This study recommends enhancing religious education and fostering collaboration between religious institutions and community leaders to deepen the understanding of marital roles in accordance with Islamic teachings.